A novel approach to reduce radial artery occlusion after transradial catheterization: Postprocedural/prehemostasis intra‐arterial nitroglycerin. Issue 5 (13th September 2014) - Dharma, Surya; Kedev, Sasko; Patel, Tejas; Kiemeneij, Ferdinand; Gilchrist, Ian C.
Abstract : Objective: To evaluate whether administration of nitroglycerin through the sheath at the end of a transradial procedure might preserve the patency of the radial artery. Background: Despite the increasing acceptance of transradial approach, radial artery occlusion (RAO) continues to be a vexing problem of transradial access and limits utility of the radial artery as an access site in the future. Methods: We conducted a multicenter, prospective, randomized, placebo‐controlled, operator‐blinded trial and enrolled 1, 706 patients who underwent transradial catheterization in three experienced radial centers. Patients were randomized to receive either 500 µg nitroglycerin (n = 853) or placebo (n = 853), given intra‐arterially through the sheath at the end of the radial procedure. The primary outcome was the incidence of RAO as confirmed by absence of antegrade flow at one day after the transradial procedure evaluated by duplex ultrasound of the radial artery. Results: The use of nitroglycerin, as compared with placebo, reduced the risk of the primary outcome [8.3% vs. 11.7%; odds ratio, 0.62; 95% confidence interval (CI), 0.44–0.87; P = 0.006]. From a multivariable analysis, duration of hemostasis was a predictor of RAO (odds ratio, (odds ratio, 3.11; 95% CI, 1.66 to 5.82; P < 0.001). There were no significant differences between the groups with respect to the sheath size (P = 0.311), number of puncture attempts (P = 0.941), duration of hemostasis (P = 0.379) and procedural time (P = 0.095). Conclusion: The administration of nitroglycerin at the end of a transradial catheterization, reduced the incidence of RAO, examined 1 day after the radial procedure by ultrasound. Postprocedural/prehemostasis pharmacologic regimens may represent a novel target for further investigation to reduce RAO. © 2014 Wiley Periodicals, Inc.